Using a wiki platform to promote guidelines internationally and maintain their currency: evidence‐based guidelines for the nutritional management of adult patients with head and neck cancer. Issue 2 (21st January 2013) - Brown, T.; Findlay, M.; von, J.; Davidson, W.; Hill, J.; Isenring, E.; Talwar, B.; Bell, K.; Kiss, N.; Kurmis, R.; Loeliger, J.; Sandison, A.; et al.
Abstract Background The present study describes the development of evidence‐based practice guidelines for the nutritional management of adult patients with head and neck cancer using a wiki platform to enable wide international stakeholder consultation and maintain currency. Methods A dietitian steering committee and a multidisciplinary steering committee were established for consultation. Traditional methods of evidence‐based guideline development were utilised to perform the literature review, assess the evidence and produce a draft document. This was transferred to a wiki platform for stakeholder consultation and international endorsement processes in Australia, New Zealand and the UK. Data were collected on website traffic utilising Google Analytics. Results In addition to broad stakeholder consultation through the steering committees, an additional twenty comments were received via the wiki by twelve individuals covering six different professions from three different countries, compared to four comments by e‐mail. The guidelines were subsequently endorsed by the dietetic associations of Australia, New Zealand and the UK. During a 4‐month period monitoring the use of the guidelines, there were 2303 page views to the landing page from 33 countries. The average number of pages accessed per visit was five and the duration of time spent on the website was approximately 6 min. Conclusions Using a wiki platform for guideline development and dissemination is a successful method for producing high‐quality resources that can undergo wide international stakeholder review and include open public consultation. This can replace conventional methods whereby guidelines can quickly become outdated.